2014
DOI: 10.1038/cmi.2014.114
|View full text |Cite
|
Sign up to set email alerts
|

Monomethyl fumarate augments NK cell lysis of tumor cells through degranulation and the upregulation of NKp46 and CD107a

Abstract: Dimethyl fumarate (DMF) is a new drug used to treat multiple sclerosis (MS) patients. Here, we examined the effects of DMF and the DMF metabolite monomethyl fumarate (MMF) on various activities of natural killer (NK) cells. We demonstrated that MMF augments the primary CD56 1 , but not CD56 2 , NK cell lysis of K562 and RAJI tumor cells. MMF induced NKp46 expression on the surface of CD56 1 , but not CD56 2 , NK cells after incubation for 24 h. This effect was closely correlated with the upregulation of CD107a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…Further antitumorigenic action of DMF could be demonstrated for glioblastoma and colon carcinoma cells . In addition, recent research demonstrated that the DMF metabolite MMF fortifies CD56 + NK cell lysis of tumor cells via degranulation and upregulation of NKp46 and CD107a . All these results illustrate that DMF seems to have potential antitumorigenic effects.…”
Section: Introductionmentioning
confidence: 84%
“…Further antitumorigenic action of DMF could be demonstrated for glioblastoma and colon carcinoma cells . In addition, recent research demonstrated that the DMF metabolite MMF fortifies CD56 + NK cell lysis of tumor cells via degranulation and upregulation of NKp46 and CD107a . All these results illustrate that DMF seems to have potential antitumorigenic effects.…”
Section: Introductionmentioning
confidence: 84%
“…NK cell activation requires the integration of signals from activating and inhibitory receptors [ 12 , 57 , 58 ]. Our cultured NK cells express numerous activating receptors (NKp46, NKp30, and NKG2D) and co-activating receptors (SFRs) to ensure their function.…”
Section: Discussionmentioning
confidence: 99%
“…Several cytokines and immunomodulatory drugs, such as the common g-chain family of cytokines (interleukin (IL)-2, IL-7, IL-15, and IL-21), thalidomide, and pomalidomide, boost NK-cell cytotoxicity [43,44]. However, the targets of these cytokines and drugs vary [45].…”
Section: Cytokines and Immunomodulatory Drugsmentioning
confidence: 99%